Effects of green authenticity on well-being, customer engagement and approach behavior toward green hospitality brands - Yu, Jongsik; Baah, Nancy Grace; Kim, Seongseop; Moon, Hyoungeun; Chua, Bee-Lia; Han, Heesup (Emerald, 2024)
Purpose This study aims to develop a robust theoretical framework to explain the impact of hotels’ green brand authenticity on guests’ perceptions of well-being, customer engagement and approach behaviors toward green brands.